Encyclopedia of mathematics and society [ - Greenwald, Sarah J.; Thomley, Jill E. (Salem Press, 2012)
Presents articles showing the math behind our daily lives. Explains how and why math works, and allows readers to better understand how disciplines such as algebra, geometry, calculus, and others affect what we do every day.